2016
DOI: 10.1001/jamapsychiatry.2016.2619
|View full text |Cite
|
Sign up to set email alerts
|

The 40-Hz Auditory Steady-State Response in Patients With Schizophrenia

Abstract: The 40-Hz ASSR spectral power and phase-locking deficits are robust in schizophrenia, which suggests that these measures could be useful probes for assessing circuit dysfunctions in the disorder. Moreover, these findings should motivate large-scale studies of the longitudinal expression in patients with schizophrenia and at-risk populations, to further validate the 40-Hz ASSR as a potential biomarker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
213
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 237 publications
(257 citation statements)
references
References 69 publications
28
213
3
Order By: Relevance
“…This is an important finding, given the increasing use of the ASSR as a biomarker in investigations of neuropsychiatric disorders (O’Donnell et al, 2013; Sivarao et al, 2016; Thune et al, 2016). Consistent with our previous findings with EEG data (McFadden et al, 2014), we found the ASSR to be reliable across two sessions, spaced approximately one week apart.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…This is an important finding, given the increasing use of the ASSR as a biomarker in investigations of neuropsychiatric disorders (O’Donnell et al, 2013; Sivarao et al, 2016; Thune et al, 2016). Consistent with our previous findings with EEG data (McFadden et al, 2014), we found the ASSR to be reliable across two sessions, spaced approximately one week apart.…”
Section: Discussionmentioning
confidence: 78%
“…Although it is more common to measure in sensor space in the EEG literature, certain ERP measures also appear to benefit from source-analysis related improvement in signal-to-noise ratio and test-retest reliability (e.g., see Segalowitz et al, 2010). As much of the literature involving the use of the ASSR as a biomarker in studies of neuropsychiatric disorders uses source-space projected data, at least when the imaging technique is MEG (e.g., see meta-analysis of EEG and MEG ASSR from Thune et al, 2016), we felt it would be more applicable to assess reliability of this measure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until recently, the large body of work implicating abnormal gamma band activity in ScZ has focused on rhythmic activity in the 40-Hz frequency range with EEG. The most consistent evidence from these studies is a reduction in both amplitude and phase locking of 40-Hz auditory steady-state responses (39, 40). …”
Section: Meg Studies In Neuropsychiatric Disordersmentioning
confidence: 78%